The Influence Of Parental Example On The Formation Of Moral Association Of Grade Xi Students At Man 2 Sumedang - Arghi Rivaldy Ramadhan; Dian Sukmara; Moch. Hilman Taabudilah (International Journal of Social Sciences, 2026)
Character development is a primary goal in education. Amidst the rapid flow of information and the development of social media, students are faced with the challenge of being able to filter information wisely. One important virtue that needs to be instilled is social etiquette, which is a concept in Islam that governs how a Muslim should interact and socialize with others, whether in the family environment, friendships, or the wider community. This character is very important in maintaining the harmony of social relationships and preventing the emergence of conflict. Therefore, to achieve this, a parental example is needed, which is the good example shown by parents in their words, actions, attitudes, and way of thinking, which is then followed by their children. This research aims to determine the Influence of Parental Role Modeling on the Formation of Social Morality in 11th-grade Students at MAN 2 Sumedang. This research uses a quantitative approach, with the research subjects being the students of class XI at MAN 2 Sumedang in the 2024/2025 academic year, with a population of 100 people. The researcher took a sample of 20%, resulting in a sample size of 20 people. The research results show that the role modeling of parents of class The relationship between parental role modeling and the formation of students' social morals shows a moderately strong positive correlation (r=0.499), with a contribution of 20.2% (r2=20.2%). The influence of parental role modeling on the formation of social morals of class XI students at MAN 2 Sumedang is proven to be significant. This research is expected to contribute to the development of literature and insights in its field.